Political pressure, rhetoric and monetary policy : lessons for the European Central Bank - Maier, Philipp (Cheltenham, UK ; Northampton, MA, USA : E. Elgar Pub., 2002)
This book provides fresh perspective on the external triangle of government, the fiancial sector and monetary authority. Egually important are the autor's innovative analyses which provide a greater understanding of the future prospects and challenges for the European Central Bank, at a time when Europe's key monetary institution faces the impact of a broadening EMU'.
Includes bibilographical references (p. 203-220) and indexes.
gau 23/06/14
Loans
Keywords: Banks and banking, Central -- Political aspects; Monetary policy -- European Union countries; Banks and banking, Central -- European Union countries; Banks and banking, Central